Hubungan antara Komitmen Organisasi dengan Kinerja Guru SD Metta Maitreya Pekanbaru - Yadi Sutikno; Hosan Hosan; Irawati Irawati (Jurnal Maitreyawira, 2020)
This research is motivated by the performance of the teachers at SD Metta Maitreya which are still not professional, there are still scores of students under the KKM, and a lack of organizational commitment to school teachers, and there are still teachers who lack teacher responsibility at work. Therefore, this study aims to determine the relationship between organizational commitment and organizational culture with the performance of teachers at SD Metta Maitreya Pekanbaru. The research method used is a survey method with correlational techniques. The study population was 24 teachers of SD Metta Maitreya Pekanbaru, so the sample was 24 people. The data collection instrument was in the form of a questionnaire or questionnaire. The validity and reliability of the questionnaire on performance, organizational commitment, and organizational culture have been tested. The data normality test was carried out by the Kolmogorov Smirnov test. The data analysis used was multiple correlation analysis using a level of α = 0.05. The results of data analysis show that there is a significant relationship between Organizational Commitment (X1) and Organizational Culture (X2) and Teacher Performance (Y) together with the regression equation Y = 81.388 + 0.295X1 + 0.466X2, the correlation coefficient is 0.570. The results of this study are expected to be useful for improving the performance, organizational commitment and organizational culture of SD Metta Maitreya Pekanbaru. The conclusion of this study shows that performance can be increased through increasing organizational commitment and organizational culture simultaneously.